Natural products-based: Synthesis and antifungal activity evaluation of novel L-pyroglutamic acid analogues - Ai, Likun; Fu, Shiqi; Li, Yong; Zuo, Mei; Huang, Wen; Huang, Jian; Jin, Zhichao; Chen, Yang (Frontiers in Plant Science, 2022)
Botanical pesticides are one of the sources of third-generation pesticides, which have received much attention at home and abroad in recent years due to their degradable and pollution-free advantages in nature. Our group explored a concise approach toward synthesizing a series of novel L-pyroglutamic acid analogs from L-hydroxyproline. Furthermore, this paper investigated antifungal activity of these sulfonyl ester derivatives on hydroxyl against Pyricularia oryzae, Fusarium graminearum, Alternaria brassicae, Valsa mali, and Altenaria alternariae. Bioassay studies showed that most compounds show moderate antifungal activity. For instance, C08a and C08l showed the best activity against Fusarium graminearum. This study suggests that compound C08n could be used as a potential lead compound to control Fusarium graminearum.